2017
DOI: 10.1016/j.sjbs.2017.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO and Rh blood groups with breast cancer

Abstract: Blood group "A" and "Rhesus +ve" have high risk of breast cancer, while blood type "AB" and "Rhesus -ve" are at low peril of breast cancer. Physicians should carefully monitor the females with blood group "A" and "Rh +ve" as these females are more prone to develop breast cancer. To reduce breast cancer incidence and its burden, preventive and screening programs for breast cancer especially in young women are highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 18 publications
11
76
0
2
Order By: Relevance
“…In the present study, data from 243 number of cases and 250 controls, we found significant associations of blood group A with increased risk of Cancer in Eastern (U.P.). Studies across the word has shown association of blood group A with, Breast Cancer (18)(19)(20)(21), pancreatic cancer (22)(23)(24)(25), liver Cancer (26) gastric and lung Cancer (27,28,29,32,33,34) risk. Data from a these studies have shown that blood group A is associated with breast cancer, liver and pancreatic cancer, and lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, data from 243 number of cases and 250 controls, we found significant associations of blood group A with increased risk of Cancer in Eastern (U.P.). Studies across the word has shown association of blood group A with, Breast Cancer (18)(19)(20)(21), pancreatic cancer (22)(23)(24)(25), liver Cancer (26) gastric and lung Cancer (27,28,29,32,33,34) risk. Data from a these studies have shown that blood group A is associated with breast cancer, liver and pancreatic cancer, and lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Another study suggested that people with blood group B have greater risk of developing T2DM and blood group O has lowest risk. 17 However there are studies that shows positive association of T2DM with blood group A. 18,19 Gestational diabetes is more prevalent in patients with blood group AB.…”
Section: Discussionmentioning
confidence: 99%
“…Plague [14] Low O 17 H.pylori infection &GI Ulceratio n [14 ] High O 18 Diabetes mellitus type 2 (15) High B…”
Section: Blood Group and Diseasesmentioning
confidence: 99%